Change in Gasdermin-D gene expression in familial Mediterranean fever compared to healthy children with or without acute infections - Pınar Özge Avar Aydın; İsmail Yaz; Dilan İnan; Zeynep Birsin Özçakar; Sevil Oskay Halaçlı; Deniz Çağdaş (The Turkish Journal of Pediatrics)
Background. Gasdermin-D (GSDMD) is an inflammasome regulator. Pyroptosis and GSDMD-mediated interleukin (IL)-1β secretion abolish in GSDMD-deficient familial Mediterranean fever (FMF) knock-in mice. We aimed to investigate GSDMD gene expression (GSDMD-∆), acute phase reactants (APRs), serum IL-1β, and IL-18 levels in FMF patients during attacks and attack-free periods.